Crystallization, preliminary X-ray diffraction studies and Raman microscopy of the major haemoglobin from the sub-Antarctic fish Eleginops maclovinus in the carbomonoxy form. - MERLINO, ANTONELLO; MAZZARELLA, LELIO; VERGARA, ALESSANDRO; Vitagliano L; Balsamo A; Nicoletti FP; Howes BD; Giordano D; Coppola D; di Prisco G; Verde C; Smulevich G (Acta Crystallographica Section F Structural Biology and Crystallization Communications, 2010)
The blood of the sub-Antarctic fish Eleginops maclovinus (Em) contains three haemoglobins. The major haemoglobin (Hb1Em) displays the Root effect, a drastic decrease in the oxygen affinity and a loss of cooperativity at acidic pH. The carbomonoxy form of HbEm1 has been crystallized in two different crystal forms, orthorhombic (Ortho) and hexagonal (Hexa), and high-resolution diffraction data have been collected for both forms (1.45 and 1.49 A ̊ resolution, respectively). The high-frequency resonance Raman spectra collected from the two crystal forms using excitation at 514 nm were almost indistinguishable. Hb1Em is the first sub-Antarctic fish Hb to be crystallized and its structural characterization will shed light on the molecular mechanisms of cold adaptation and the role of the Root effect in fish haemoglobins.